Roman Satire - Ferriss-Hill, Jennifer (Brill Research Perspectives in Humanities and Social Sciences., 2022)
How do you insert yourself into an artistic canon? How do you establish yourself as a worthy successor to your predecessors while making your own mark on a genre? How do you police a genre's boundaries to keep out the unwanted? With particular attention to authorial and national identity, artistic self-definition, and literary reception, this volume shows how four ancient Latin poets-Lucilius, Horace, Persius, and Juvenal-asked and answered these questions between the second century BCE and the second century CE as they invented and reinvented the genre of Roman verse Satire.